The Anastomosis of Austrian Entrepreneurship with Organizational Agility - Barcaui, Andre (2021)
This paper seeks to analyze the concepts of entrepreneurship at the Austrian School under the lens ofa contemporary management format called “agility.” The methodological procedure adopted was theoretical,with an exploratory and descriptive character using a bibliographic review of the leading Austrian authorsand a bibliometric survey of publications related to agility. From an analytical-interpretative reading, it did an associative analysis of Austrian entrepreneurship with agility. The research findings suggest that the Austrian authors at several points anticipated the ideas proposed by business agility, particularly concerning value creation, customer focus, and adaptation.